Combining Repetitive Transcranial Magnetic Stimulation and Video Game-Based Training to Improve Dexterity in Parkinson's Disease: Study Protocol of a Randomized Controlled Trial - Pastore-Wapp, Manuela; Lehnick, Dirk; Nef, Tobias; Bohlhalter, Stephan; Vanbellingen, Tim (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Patients with Parkinson's disease (PD) often exhibit difficulties with dexterity during the performance of activities of daily living (ADL) due to dysfunctional supplementary motor area (SMA). The aim of this clinical trial protocol work is to describe how the effectiveness of a combined repetitive transcranial magnetic stimulation (rTMS) over SMA and video-game-based skill training (VBT) in PD will be evaluated. The short and long-term benefits are assessed. Methods and analysis: A single-blind (patients) stratified (based on Hoehn & Yahr) parallel randomized sham-controlled rTMS-VBT study with a baseline and two follow-up measurements (3 and 12 weeks) is being conducted. These measurements include the dexterity questionnaire 24 (DextQ-24) as a primary outcome, and nine hole peg test and coin rotation task as main secondary dexterity outcomes. Further secondary outcomes will be the subscale II of the movement disorders society unified PD rating scale (MDS-UPDRS) to assess improvements on overall ADL and the Parkinson's Disease Questionnaire-39 to assess quality of life. Thirty-six outpatients (from one neurorehabilitation center) with PD (diagnosis based on brain bank criteria) will be recruited who report difficulties with dexterity in performing ADL. All PD patients will receive a 45-min VBT three times a week for 3 weeks. The PD patients randomized in the experimental group will receive VBT preceded by real rTMS, being intermittent theta burst (iTBS) stimulation sessions. The PD patients randomized to the control group receive a VBT with sham rTMS. Discussion: The study will provide evidence to determine whether a combined iTBS and VBT skill intervention is more effective than a VBT intervention alone to improve dexterity in PD. Ethics and dissemination: The study was approved by the Ethics Committee for Northwest and Central Switzerland (EKNZ), Switzerland 2019–00433. The study will be conducted in accordance with the Helsinki Declaration and the Guidelines of Good Clinical Practice. Informed consent will be signed prior to subject enrolment. Dissemination will include submission to international peer-reviewed professional journals and presentation at international congresses. The study protocol has been registered in the clinicaltrials.gov registry with the identification code: NCT04699149.